Finite-element model of a sole with the using of cellular objects - V. V. Naprasnikov; I. L. Kovaleva; Y. V. Polozkov; D. P. Kunkevich; A. V. Borodulya (Системный анализ и прикладная информатика, 2023)
One of the possible approaches to the formation of the optimization model of the underlay is the use of cellular objects. At the same time, the question of constructing geometric models of such objects is relevant. Code fragments and construction results for one variant of geometry in IronPython language in SpaceClaim environment to solve such a problem are given. A possible approach to solving the problem of forming boundary conditions changing in time and space is described.